Territory acquisition mediates the influence of predators and climate on juvenile red squirrel survival. Issue 6 (19th April 2020) - Hendrix, Jack G.; Fisher, David N.; Martinig, April Robin; Boutin, Stan; Dantzer, Ben; Lane, Jeffrey E.; McAdam, Andrew G.
Abstract: Juvenile survival to first breeding is a key life‐history stage for all taxa. Survival through this period can be particularly challenging when it coincides with harsh environmental conditions such as a winter climate or food scarcity, leading to highly variable cohort survival. However, the small size and dispersive nature of juveniles generally make studying their survival more difficult. In territorial species, a key life‐history event is the acquisition of a territory. A territory is expected to enhance survival, but how it does so is not often identified. We tested how the timing of territory acquisition influenced the winter survival of juvenile North American red squirrels Tamiasciurus hudsonicus, hereafter red squirrels, and how the timing of this event mediated the sources of mortality. We hypothesized that securing a territory prior to when food resources become available would reduce juvenile susceptibility to predation and climatic factors overwinter. Using 27 years of data on the survival of individually marked juvenile red squirrels, we tested how the timing of territory acquisition influenced survival, whether the population density of red squirrel predators and mean temperature overwinter were related to individual survival probability, and if territory ownership mediated these effects. Juvenile red squirrel survival was lower in the years of high predator abundance and in colder winters. Autumn territory owners were less susceptible to lynx Lynx canadensis and possibly mustelid Mustela and Martes spp., predation. Autumn territory owners had lower survival in colder winters, but surprisingly non‐owners had higher survival in cold winters. Our results show how the timing of a life‐history event like territory acquisition can directly affect survival and also mediate the effects of biotic and abiotic factors later in life. This engenders a better understanding of the fitness consequences of the timing of key life‐history events. Abstract : The authors examine how territories, predators and climate influenced the winter survival of juvenile North American red squirrels over three decades. Territory owners survived better and were less affected by lynx abundance, but territories did not improve survival over colder winters. They provide insights into the understudied life stage of first independence.